Experimental and theoretical studies of aeroacoustics damping performance of a bias-flow perforated orifice. (February 2019) - Zhao, Dan; Sun, Yuze; Ni, Siliang; Ji, Chenzhen; Sun, Dakun
Abstract: Aeroacoustics damping performance of an in-duct perforated orifice with a bias flow in terms of acoustic power absorption Δ and reflection χ coefficients are evaluated in this work. For this, experimental measurements of a cold-flow pipe system with a diameter of 2 b with an in-duct perforated plate implemented are conducted over the frequency range of 100 to 1000 Hz first. The effects of (1) the downstream pipe length L d, (2) porosity η, (3) bias flow Mach number M a and (4) the orifice thickness l w are experimentally evaluated on affecting the noise damping performance of the in-duct perforated orifice. It is found that decreasing L d leads to increased Δ max (maximum power absorption). However, the orifice thickness plays a negligible effect at lower frequency, and a non-negligible role at higher frequency range. The maximum power absorption Δ max and reflection coefficients χ max are found to be approximately 80% and 90% respectively. There is an optimum porosity or Mach number corresponding to Δ max . In addition, Δ and χ are periodically changed with the forcing frequency. To simulate the experiments and gain insights on the damping performance of the orifice with a diameter of 2 a, an 1D theoretical model that embodies vorticity-involved noise absorption mechanism is developed. It is based on the modified form of the Cummings equation describing unsteady flow through an orifice and the Cargill equation describing acoustically open boundary condition at the end of the downstream duct. It is shown that Δ and χ are strongly related to (1) the bias flow Mach number M a, (2) forcing frequency ω, (3) porosity η, (4) and the downstream pipe length L d . Comparing with the experimental measurements reveals that good agreement is obtained. This confirms that the present experimental and theoretical study shed lights on the optimum design of in-duct orifices.